Digital platforms and SMEs’ business model innovation: Exploring the mediating mechanisms of capability reconfiguration - Xie, Xuemei; Han, Yuhang; Anderson, Alistair; Ribeiro-Navarrete, Samuel (International journal of information management, 2022)
In our digital era, many small and medium-sized enterprises (SMEs) face the challenge of relying on digital platforms to enhance their business model innovation. Prior research on this subject has mainly focused on the interaction between SMEs and their partners through their use of digital platforms. Meanwhile, how SMEs reconfigure their capabilities to promote business model innovation by adopting digital platforms has remained an under-researched area. To address this gap, we establish a conceptual framework to explain how digital platforms affect SMEs’ business model innovation through capability reconfiguration, and we then test this conceptual framework empirically by using a sample of 325 manufacturing SMEs in China. We find that digital platforms positively affect both business model innovation and the capability reconfiguration of SMEs. We also find that both evolutionary capability reconfiguration and substitutional capability reconfiguration mediate the relationship between digital platforms and SMEs’ business model innovation. These findings contribute theoretically to the research on digital platforms and SMEs while also providing important managerial implications for policymakers and SMEs to help firms implement digital strategies. •We examine the effect of digital platforms on business model innovation (BMI).•We examine the effect of digital platforms on capability reconfiguration (CR).•Evolutionary CR mediates the effect of digital platforms on BMI.•Substitutional CR mediates the effect of digital platforms on BMI.